Nghiên cứu hữu cơ hóa clay tuy phong bằng axit aminotrimetylphotphonic - Xuân Hằng, Tô Thị; Trúc, Trịnh Anh; Nam, Trương Hoài; Nghĩa, Nguyễn Đức (Vietnam Journal of Chemistry, 2014)
Clay montmorillonite from Tuy Phong with the cation exchange capacity of 90-120 meq/100 g was organically modified by cation exchange reaction with acid aminotrimethylphosphonic. The clay modified was characterized by infrared spectroscopy, X-ray diffraction and scanning electronic microscopy. The corrosion protection ability of modified clay was evaluated by corrosion potential measurement. Structure analyze by infrared spectroscopy indicated that characteristic vibration bands showed at 1464 cm-1 and 2960 cm-1 (C-H) of ATMP were also found in the spectra of clay-ATMP. XRD analyze showed that the d001 spacing of clay-ATMP was about 3,19 higher then that of pristine clay. These results indicate the intercalation of ATMP molecules between clay layers. SEM observation demonstrated that in clay-ATMP the silicate platelets are better separated then in pristine clay. Electrochemical measurements of corrosion potential indicated that in clay-ATMP solution the corrosion potential of steel electrode was higher the in clay solution and it is closed to the one of ATMP solution. A protective film was form on steel surface after 2 hours of immersion clay-ATMP solution. SEM observation indicated the film formed has the similar structure like clay-ATMP, the silicates platelets covered the steel surface